P-type AlGaN material and preparation method thereof, and preparation method of ultraviolet photoelectronic device

By using temperature differences to escape Ga atoms to form cation vacancy during the growth of p-type AlGaN materials, the concentration of acceptor impurities is increased, thereby solving the problem of lowering hole concentration in p-type AlGaN materials, and improving material performance and improving device performance are achieved.

CN119133328BActive Publication Date: 2025-03-11SUZHOU LEKIN SEMICON CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411579154.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-11
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The activation energy of the acceptor impurity atoms in existing p-type AlGaN materials increases, resulting in a decrease in the concentration of hole carriers, limiting the application of the material and device performance.

Method used

By growing a p-type AlGaN material at a first temperature and suspending the inflow of the organometallic source at an environment where the second temperature is higher than the first temperature of 20°C to 200°C, some Ga atoms escape to form cationic vacancy, increasing the concentration of the acceptor impurities, thereby increasing the hole concentration.

Benefits of technology

It effectively improves the hole concentration of p-type AlGaN materials, improves the performance of the material, reduces the contact resistance, and improves the luminous efficiency and photoelectric conversion efficiency of ultraviolet photoelectronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133328B_ABST
    Figure CN119133328B_ABST
Patent Text Reader

Abstract

The present application relates to a p-type AlGaN material and a preparation method thereof, and a preparation method of an ultraviolet photoelectronic device, and belongs to the field of semiconductor technology. The preparation method of the p-type AlGaN material comprises: introducing an organic metal source and an N source at a first temperature to grow the p-type AlGaN material; pausing the introduction of the organic metal source and maintaining the temperature at a second temperature for a certain period of time to allow some Ga atoms in the p-type AlGaN material to escape, thereby generating cation vacancies in the p-type AlGaN material; wherein the second temperature is higher than the first temperature, and the difference between the second temperature and the first temperature ranges from 20°C to 200°C. Thus, the hole concentration of the p-type AlGaN material is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of semiconductor technology, and in particular to a method for preparing a p-type AlGaN material, a method for preparing a p-type AlGaN material and an ultraviolet optoelectronic device. Background Art

[0002] At present, the third-generation semiconductor materials represented by AlN and GaN are widely used in optoelectronic devices such as LED (Light Emitting Diode) and LD (Laser Diode). Among them, AlGaN, as an alloy material of AlN and GaN, plays a key role in ultraviolet and far-ultraviolet optoelectronic devices due to its tunable band gap characteristics.

[0003] In the device, p-type AlGaN material can be used as a p-type electrode contact layer. By adjusting the Al component ratio, the material band gap can be tuned to improve the luminous efficiency. The p-type AlGaN material can also be used as an electron blocking layer. By adjusting the Al component ratio, it has a wide bandgap and a high potential barrier, thereby blocking the leakage of electrons from the n-type layer or multi-quantum well layer to the p-type layer. However, as the Al component ratio increases, the activation energy of the acceptor impurity atoms in the p-type AlGaN material becomes higher, making it difficult to excite and generate enough hole carriers, which reduces the hole concentration of the material, restricting the application of p-type AlGaN materials and affecting the performance of the device.

[0004] Therefore, how to increase the hole concentration of p-type AlGaN materials has become an urgent problem to be solved in this field. Summary of the invention

[0005] In view of this, embodiments of the present application provide a method for preparing a p-type AlGaN material, a method for preparing a p-type AlGaN material and an ultraviolet optoelectronic device to solve at least one problem existing in the background technology.

[0006] In a first aspect, an embodiment of the present application provides a method for preparing a p-type AlGaN material, comprising:

[0007] At a first temperature, an organic metal source and an N source are introduced to grow a p-type AlGaN material;

[0008] The organic metal source is suspended and maintained at a second temperature for a certain period of time to allow some Ga atoms in the p-type AlGaN material to escape, thereby generating cation vacancies in the p-type AlGaN material; wherein the second temperature is higher than the first temperature, and the difference between the second temperature and the first temperature ranges from 20°C to 200°C.

[0009] In conjunction with the first aspect of the present application, in an optional embodiment, the organic metal source includes an acceptor impurity source;

[0010] After suspending the introduction of the organic metal source and maintaining it at the second temperature for a certain period of time, the preparation method further comprises: suspending the introduction of other metal sources in the organic metal source except the acceptor impurity source, and only introducing the acceptor impurity source, so that the acceptor impurity occupies the cation vacancy.

[0011] In conjunction with the first aspect of the present application, in an optional implementation, the step of suspending the introduction of other metal sources in the organic metal source except the acceptor impurity source and only introducing the acceptor impurity source comprises:

[0012] At a third temperature, the introduction of other metal sources in the organic metal source except the acceptor impurity source is stopped, and only the acceptor impurity source is introduced; wherein the third temperature is lower than or equal to the second temperature.

[0013] In combination with the first aspect of the present application, in an optional implementation manner, the difference between the third temperature and the first temperature is in the range of ±10°C.

[0014] In conjunction with the first aspect of the present application, in an optional implementation, the first temperature ranges from 900°C to 1150°C.

[0015] In combination with the first aspect of the present application, in an optional embodiment, the organic metal source includes an Al source, a Ga source, an In source and a Mg source, and the amount of the In source introduced is less than the amount of the Ga source introduced;

[0016] The step of introducing an organic metal source and an N source to grow a p-type AlGaN material comprises: introducing the Al source, the Ga source, the In source, the Mg source and the N source to grow an In-doped p-type AlGaN material;

[0017] The suspending the introduction of the organic metal source to allow some Ga atoms in the p-type AlGaN material to escape includes: suspending the introduction of the Al source, the Ga source, the In source and the Mg source to allow In atoms and some Ga atoms in the p-type AlGaN material to escape; wherein the escape amount of the In atoms is less than the escape amount of the Ga atoms.

[0018] In combination with the first aspect of the present application, in an optional implementation manner, the amount of the In source introduced ranges from 20 sccm to 100 sccm.

[0019] In combination with the first aspect of the present application, in an optional implementation manner, the p-type AlGaN material is at least one of an electron blocking layer, a hole injection layer and an ohmic contact layer.

[0020] In combination with the first aspect of the present application, in an optional implementation manner, the growing the p-type AlGaN material includes: growing the p-type AlGaN material at a growth rate ranging from 0.05 μm / h to 0.35 μm / h.

[0021] In conjunction with the first aspect of the present application, in an optional implementation manner, the time ranges from 5s to 50s.

[0022] In conjunction with the first aspect of the present application, in an optional implementation manner, the time ranges from 10s to 20s.

[0023] In conjunction with the first aspect of the present application, in an optional implementation, the Al component of the p-type AlGaN material is greater than 20% to 90%;

[0024] The preparation method further includes: introducing a carrier gas; wherein the carrier gas includes a mixed carrier gas composed of N2 and H2, and the proportion of N2 in the mixed carrier gas ranges from 10% to 45%.

[0025] In combination with the first aspect of the present application, in an optional implementation, the proportion of N2 in the mixed carrier gas ranges from 15% to 25%.

[0026] In a second aspect, an embodiment of the present application provides a p-type AlGaN material, which is prepared using the method for preparing the p-type AlGaN material as described in any one of the first aspects.

[0027] In a third aspect, an embodiment of the present application provides a method for preparing an ultraviolet photoelectronic device, comprising:

[0028] The first step of preparing the main structure of the ultraviolet optoelectronic device, and

[0029] A second step of preparing an electrode that cooperates with the main structure;

[0030] The first step includes:

[0031] The p-type AlGaN material is prepared by the method for preparing the p-type AlGaN material according to any one of the first aspects, so as to increase the hole concentration of the p-type AlGaN material.

[0032] The present invention provides a method for preparing a p-type AlGaN material, a p-type AlGaN material and an ultraviolet photoelectronic device. At a first temperature, an organic metal source and an N source are introduced to grow a p-type AlGaN material; the introduction of the organic metal source is suspended, and the temperature is maintained at a second temperature for a certain period of time to allow some Ga atoms in the p-type AlGaN material to escape, thereby generating cation vacancies in the p-type AlGaN material; wherein the second temperature is higher than the first temperature, and the difference between the second temperature and the first temperature ranges from 20°C to 200°C. Thus, by increasing the first temperature by 20°C to 200°C, Ga atoms in the p-type AlGaN material are allowed to escape under the second temperature environment, and cation vacancies are introduced into the material; by suspending the introduction of the organic metal source, atoms in the organic metal source are prevented from filling the formed cation vacancies, thereby ensuring the concentration of cation vacancies in the material; under the synergistic effect of the two, a large number of cation vacancies can be formed in the material by maintaining the temperature for a certain period of time, thereby increasing the concentration of acceptor impurities in the p-type AlGaN material, thereby increasing the hole concentration of the p-type AlGaN material, and improving the material performance. When growing the material, a trace amount of In source is introduced to generate In-doped p-type AlGaN material. In acts as a catalyst, affecting the mobility of Mg atoms on the crystal surface, making it easier for them to migrate to replace Al atoms or Ga atoms, thereby increasing the doping concentration. At the second temperature, In atoms also escape from the lattice position, leaving cation vacancies, further increasing the vacancy concentration. In addition, a mixed carrier gas composed of N2 and H2 is introduced during the preparation process, thereby avoiding the problem of pure H2 carrier gas affecting the incorporation of Mg atoms, and also avoiding the problem of pure N2 carrier gas affecting the crystal quality and hole concentration. The doping amount of Mg atoms can be increased while ensuring the crystal quality, and the synergistic effect of the two can further improve the material performance.

[0033] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0035] Figure 1 A schematic diagram of a process for preparing a p-type AlGaN material provided in an embodiment of the present application;

[0036] Figure 2 A schematic diagram of the change in the amount of organic metal source introduced during the preparation of the p-type AlGaN material provided in the embodiment of the present application;

[0037] Figure 3A schematic diagram of temperature changes during the preparation of the p-type AlGaN material provided in an embodiment of the present application;

[0038] Figure 4 A schematic diagram of the change in the amount of N source introduced during the preparation of the p-type AlGaN material provided in an embodiment of the present application;

[0039] Figure 5 A schematic diagram of the change of the amount of carrier gas introduced during the preparation of the p-type AlGaN material provided in the embodiment of the present application;

[0040] Figure 6 It is a schematic diagram of a circular transmission ring model composed of rings of different sizes;

[0041] Figure 7 This is the electron microscope image of sample 1 in experiment 1;

[0042] Figure 8 This is the electron microscope image of sample 2 in experiment 1;

[0043] Fig. 9 This is the electron microscope image of sample 3 in experiment 1;

[0044] Fig.10 It is a line graph showing the relationship between the second temperature and the specific contact resistivity in Experiment 2;

[0045] Fig.11 This is a line graph showing the relationship between time and specific contact resistivity in Experiment 3. DETAILED DESCRIPTION

[0046] The exemplary embodiments disclosed in the present application will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the specific embodiments described herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present application and to fully convey the scope disclosed in the present application to those skilled in the art.

[0047] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and structures are not described in detail.

[0048] In the drawings, the sizes of layers, regions, elements and their relative sizes may be exaggerated for clarity. Like reference numerals denote like elements throughout.

[0049] It should be understood that when an element or layer is referred to as "on ...", "adjacent to ...", "connected to" or "coupled to" other elements or layers, it can be directly on, adjacent to, connected to or coupled to other elements or layers, or there can be intervening elements or layers. On the contrary, when an element is referred to as "directly on ...", "directly adjacent to ...", "directly connected to" or "directly coupled to" other elements or layers, there is no intervening element or layer. It should be understood that although the terms first, second, third, etc. can be used to describe various elements, components, regions, layers and / or parts, these elements, components, regions, layers and / or parts should not be limited by these terms. These terms are only used to distinguish one element, component, region, layer or part from another element, component, region, layer or part. Therefore, without departing from the teachings of the present application, the first element, component, region, layer or part discussed below can be represented as the second element, component, region, layer or part. And when the second element, component, region, layer or part is discussed, it does not indicate that the present application necessarily has the first element, component, region, layer or part.

[0050] Spatial relationship terms such as "under", "below", "below", "under", "above", "above", etc., may be used here for convenience of description to describe the relationship between an element or feature shown in the figure and other elements or features. It should be understood that in addition to the orientation shown in the figure, the spatial relationship terms are intended to include different orientations of the device in use and operation. For example, if the device in the accompanying drawings is turned over, then the elements or features described as "under other elements" or "under it" or "under it" will be oriented as "on" other elements or features. Therefore, the exemplary terms "under" and "under" may include both upper and lower orientations. The device can be oriented otherwise (rotated 90 degrees or other orientations) and the spatial descriptors used herein are interpreted accordingly.

[0051] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "one", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.

[0052] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.

[0053] Figure 1 The schematic diagram of the process of preparing the p-type AlGaN material provided in the embodiment of the present application is shown in the figure. As shown in the figure, the method for preparing the p-type AlGaN material provided in the embodiment of the present application includes:

[0054] S101: introducing an organic metal source and an N source at a first temperature to grow a p-type AlGaN material;

[0055] S102: Pause the introduction of the organic metal source and maintain the temperature at a second temperature for a certain period of time to allow some Ga atoms in the p-type AlGaN material to escape, thereby generating cation vacancies in the p-type AlGaN material; wherein the second temperature is higher than the first temperature, and the difference between the second temperature and the first temperature ranges from 20°C to 200°C.

[0056] Therefore, by increasing the first temperature by 20°C to 200°C, Ga atoms in the p-type AlGaN material are allowed to escape under the second temperature environment, thereby introducing cation vacancies in the material; by suspending the introduction of the organic metal source, atoms in the organic metal source are prevented from filling the formed cation vacancies, thereby ensuring the concentration of cation vacancies in the material; under the synergistic effect of the two, a large number of cation vacancies can be formed in the material for a certain period of time, thereby increasing the concentration of acceptor impurities in the p-type AlGaN material, thereby increasing the hole concentration of the p-type AlGaN material and improving the material performance.

[0057] It can be understood that the preparation method of the p-type AlGaN material provided in the embodiment of the present application can be a preparation method of the p-type layer of the optoelectronic device. The p-type layer of the optoelectronic device can include at least one of an electron blocking layer, a hole injection layer and an ohmic contact layer, and the p-type AlGaN material can be at least one of an electron blocking layer, a hole injection layer and an ohmic contact layer. In this embodiment, the p-type AlGaN material is specifically a hole injection layer.

[0058] It should be noted that, in the present embodiment, the p-type AlGaN material may be a p-type AlGaN-based material. In other words, it may be a material based on AlGaN but may contain other elements or compounds.

[0059] Please refer to Figures 2 to 4 In the time period from t0 to t1, step S101 is performed: at a first temperature, an organic metal source and an N source are introduced to grow a p-type AlGaN material.

[0060] The N source provides N atoms for growing AlGaN materials; the organic metal source includes a Ga source and an Al source to provide Ga atoms and Al atoms for growing AlGaN materials; and in order to obtain p-type AlGaN materials, the organic metal source also includes an acceptor impurity source, and the acceptor impurity is an impurity that can provide holes. During the growth process, Ga atoms, Al atoms and N sources form an AlGaN lattice structure, and the acceptor impurities enter the AlGaN lattice structure, replacing the original Al atoms or Ga atoms, and combining with N atoms to form covalent bonds. In this process, holes are generated to achieve p-type doping.

[0061] Since Ga atoms and Al atoms are group III atoms, they have trivalent charges. If holes are to be generated in the process of acceptor impurities replacing the original Al atoms or Ga atoms, it means that the number of valence electrons of the acceptor impurities must be less than the number of valence electrons of the Al atoms or Ga atoms. Therefore, in the process of forming covalent bonds, a charge imbalance is generated in the lattice, which is equivalent to introducing positive charges in the lattice. This positive charge can be understood as a hole. Therefore, the acceptor impurity can be any suitable acceptor impurity known to those skilled in the art, for example, any one or more combinations of Mg, Zn, Be, and C.

[0062] This embodiment specifically takes the acceptor impurity source as a Mg source as an example to explain and illustrate the technical solution of this embodiment.

[0063] In this embodiment, the Al source is specifically trimethylaluminum (TMAl), the Ga source is specifically trimethylgallium (TMGa), the Mg source is specifically bis(cyclopentadienyl)magnesium (CP2Mg), and the N source is specifically ammonia (NH3).

[0064] Optionally, the process for growing the p-type AlGaN material includes a MOCVD (Metal-Organic Chemical Vapor Deposition) process.

[0065] Optionally, the Al component of the p-type AlGaN material ranges from 20% to 90%. The band gap of the p-type AlGaN material increases with the increase of the Al component. The larger the band gap, the less light absorption and the higher the luminous efficiency. Therefore, setting the Al component range to 20% to 90% is conducive to improving the optical properties of the p-type AlGaN material. At the same time, in the p-type AlGaN material, as the Al component continues to increase, the activation energy of the Mg acceptor continues to increase, and the Mg acceptor is more difficult to be activated, which reduces the hole concentration in the material, thereby limiting the application of the p-type AlGaN material. The subsequent steps can effectively increase the hole concentration in the material, and then ensure that the p-type AlGaN material has good optical properties.

[0066] Furthermore, the Al component of the p-type AlGaN material ranges from 50% to 90% to further improve the optical properties of the p-type AlGaN material.

[0067] Optionally, refer to Figure 2 , the organic metal source includes an Al source, a Ga source, an In source and a Mg source, and the amount of the In source introduced is less than the amount of the Ga source introduced; introducing the organic metal source and the N source to grow a p-type AlGaN material, including: introducing the Al source, the Ga source, the In source, the Mg source and the N source to grow an In-doped p-type AlGaN material.

[0068] It can be understood that in this embodiment, the organic metal source also includes an In source. When growing p-type AlGaN material, a trace amount of In source is introduced, which acts as a catalyst to affect the mobility of Mg atoms on the crystal surface, making it easier for them to migrate to replace the positions of Al atoms or Ga atoms, thereby improving the doping efficiency. A smaller amount of In source is introduced to generate In-doped p-type AlGaN material to increase the doping concentration of Mg atoms in the p-type AlGaN material, thereby increasing the hole concentration.

[0069] Optionally, the range of the amount of In source input is 20sccm to 500sccm. Understandably, if the amount of In source input is too low, it may be difficult to effectively promote Mg atom doping; if the amount of In source input is too high, due to the relatively low binding energy of the In-N bond, In atoms are more likely to combine with N atoms, affecting the combination of Al atoms and Ga atoms with N atoms, breaking the stoichiometric ratio of AlGaN materials, causing the material properties to deviate from expectations, and causing changes in crystal structure and electrical properties.

[0070] Furthermore, the amount of In source introduced may range from 20 sccm to 100 sccm, which is more conducive to the growth of In-doped p-type AlGaN material to promote the formation of vacancy precursors.

[0071] In this embodiment, the In source is specifically trimethylindium (TMIn), for example.

[0072] Optionally, growing a p-type AlGaN material includes: growing a p-type AlGaN material within a growth rate range of 0.05 μm / h to 0.35 μm / h. It is understandable that during the growth of the p-type AlGaN material, if the growth rate is too fast, a large number of defects, such as vacancies or dislocations, may be present in the prepared material, which may affect the electron mobility of the material; it may also make it difficult to uniformly dope the acceptor impurities, resulting in excessively high or low doping concentrations in local areas, affecting the performance of the material. Therefore, growing at a low speed of 0.05 μm / h to 0.35 μm / h is more conducive to ensuring the doping of acceptor impurities and improving crystal quality. When the organic metal source also includes an In source, introducing the In source at a low speed stage is more conducive to the catalytic effect of In atoms, increasing the doping concentration of Mg atoms, and more conducive to the doping of In atoms, so as to better promote the formation of vacancy precursors.

[0073] Furthermore, the growth rate may be 0.1 μm / h-0.25 μm / h, thereby obtaining better doping effect and crystal quality.

[0074] Optionally, the first temperature ranges from 900°C to 1150°C. Thus, setting the first temperature within the range of 900°C to 1150°C provides a suitable temperature window for growing p-type AlGaN materials, which helps to achieve high-quality growth of materials while avoiding material defects that may be caused by excessively high temperatures; controlling the first temperature at a relatively low temperature allows Mg atoms to be better doped to increase the hole concentration of the material; when the organic metal source also includes an In source, since In atoms will escape under high temperature conditions, introducing the In source at a low temperature stage is more conducive to maintaining the stability of In atoms, so as to ensure that In atoms play a catalytic role, which is conducive to promoting the formation of vacancy precursors.

[0075] Further, the first temperature may range from 950° C. to 1020° C. Thus, better crystal quality and doping effect may be obtained.

[0076] Please refer to Figure 2 and Figure 3, in the time period from t1 to t2, step S102 is performed: the introduction of the organic metal source is suspended, and the temperature is maintained at the second temperature for a certain period of time, so that part of the Ga atoms in the p-type AlGaN material escape, thereby generating cation vacancies in the p-type AlGaN material; wherein the second temperature is higher than the first temperature, and the difference between the second temperature and the first temperature ranges from 20°C to 200°C. Thus, by increasing the first temperature by 20°C to 200°C, the Ga atoms in the p-type AlGaN material escape under the second temperature environment, and cation vacancies are introduced into the material; by suspending the introduction of the organic metal source, the atoms in the organic metal source are prevented from filling the formed cation vacancies, thereby ensuring the concentration of cation vacancies in the material; under the synergistic effect of the two, a large number of cation vacancies can be formed in the material by maintaining the temperature for a certain period of time, thereby increasing the concentration of acceptor impurities in the p-type AlGaN material, thereby increasing the hole concentration of the p-type AlGaN material, and reducing the contact resistance.

[0077] It can be understood that in the high temperature range of 20°C to 200°C higher than the first temperature, Ga atoms can obtain sufficient thermal energy to overcome the constraints of the lattice and escape from the lattice position, leaving cation vacancies. If the temperature is too high, it may cause excessive escape of Ga atoms, causing lattice distortion, atomic rearrangement, and produce undesirable phases or structures, reduce the quality of the material, affect the stability of the material, and then affect the contact resistivity; if the temperature is too low, it may make it difficult for Ga atoms to obtain sufficient thermal energy, thereby making it difficult to form sufficient cation vacancies, which is not conducive to improving the contact resistivity.

[0078] Furthermore, the second temperature is 50° C. to 150° C. higher than the first temperature. Within this temperature range, the hole concentration of the p-type AlGaN material can be improved well.

[0079] Optionally, suspending the introduction of the organic metal source to allow some Ga atoms in the p-type AlGaN material to escape includes: suspending the introduction of the Al source, Ga source, In source and Mg source to allow In atoms and some Ga atoms in the p-type AlGaN material to escape; wherein the escape amount of In atoms is less than the escape amount of Ga atoms.

[0080] It can be understood that in the time period from t0 to t1, a small amount of In source was introduced to prepare In-doped p-type AlGaN material; in the time period from t1 to t2, in the high temperature range of 20°C to 200°C higher than the first temperature, In atoms can also obtain sufficient thermal energy to overcome the constraints of the lattice and escape from the lattice position, leaving cation vacancies. In this stage, Ga atoms are the main providers of cation vacancies, but the In source as a surfactant also contributes in the second temperature stage, providing cation vacancies, further increasing the concentration of vacancies, and better forming vacancy precursors.

[0081] Furthermore, the second temperature is maintained for a certain time in a range of 5s to 50s.

[0082] Understandably, at the second temperature, the organic metal source is suspended, which changes the chemical balance in the growth process, changes the movement of atoms, and dislocations may form climbs and defects, providing conditions for the injection of Mg; at the same time, in the absence of additional Ga source supplementation, it may also make the escape of Ga atoms the main process, and also avoid other metal atoms from filling vacancies, thereby ensuring the concentration of cation vacancies in the p-type AlGaN material. In this case, a large number of cation vacancies can be formed in the material by maintaining it for a certain period of time, thereby increasing the concentration of acceptor impurities in the p-type AlGaN material, thereby increasing the hole concentration of the p-type AlGaN material and improving the material performance. If the maintenance time is too long, Ga atoms may escape excessively, causing lattice distortion and affecting the stability of the material. Long-term high-temperature treatment may also cause changes in the chemical composition of the material, leading to material degradation, affecting the electrical and optical properties of the material, and increasing energy consumption, increasing production costs, and reducing production efficiency; if the maintenance time is too short, sufficient cation vacancies may not be formed, thereby failing to effectively increase the hole concentration. Therefore, within this time range, more cation vacancies can be obtained while ensuring the quality of the material.

[0083] Furthermore, the second temperature may be maintained for a certain period of time in a range of 10s to 20s, thereby better improving the hole concentration of the material during this period of time.

[0084] Optionally, the second temperature range includes 1025°C to 1150°C. It is understandable that within the higher temperature range of 1025°C to 1150°C, Ga atoms can obtain sufficient thermal energy to overcome the constraints of the lattice and escape from the lattice position, leaving cation vacancies. If the temperature is too high, it may cause excessive escape of Ga atoms, causing lattice distortion, atomic rearrangement, and undesirable phases or structures, reducing the quality of the material and affecting the stability of the material; if the temperature is too low, it may make it difficult for Ga atoms to obtain sufficient thermal energy, making it difficult to form sufficient cation vacancies.

[0085] Furthermore, the second temperature may range from 1075° C. to 1125° C. Within this temperature range, cation vacancies may be better formed to ensure the quality of the material.

[0086] Optionally, refer to Figure 2, the organic metal source includes an acceptor impurity source; after executing step S102, the preparation method further includes: suspending the introduction of other metal sources except the acceptor impurity source in the organic metal source, and only introducing the acceptor impurity source, and the acceptor impurity occupies the cation vacancy. Therefore, in the time period from t2 to t3, only the acceptor impurity source is introduced, which can avoid other metal atoms competing with it for vacancies, ensure that the acceptor impurity has a higher doping efficiency in the formed cation vacancies; avoid introducing new defects and affecting the crystal quality of the material; by the acceptor impurity occupying the formed cation vacancies, the concentration of the acceptor impurity in the material is further increased, and the hole concentration of the material is increased; and the doping of the acceptor impurity is conducive to avoiding the influence of the cation vacancy on the stability of the material.

[0087] It can be understood that in the time period from t1 to t2, some Ga-N chemical bonds in the p-type AlGaN material are broken, Ga atoms escape, and cation vacancies are formed in the material to form vacancy precursors. In the time period from t2 to t3, when the acceptor impurity Mg atom enters the lattice, it forms a covalent bond with the N atoms around the vacancy. Since the number of valence electrons of the Mg atom is less than that of the Ga atom, holes are formed in the process of forming covalent bonds, which can then increase the hole concentration of the p-type AlGaN material. Similarly, when the organic metal source also includes an In source, since In atoms escape to provide cation vacancies in the time period from t1 to t2, the vacancy concentration in the material increases. Then, in the time period from t2 to t3, under the condition of a large number of vacancies in the material, Mg atoms enter the substitution position. Since the number of valence electrons of the Mg atom is less than that of the In atom, holes are also formed in the process of forming covalent bonds, thereby further increasing the hole concentration of the material.

[0088] Optionally, refer to Figure 3 , suspending the introduction of other metal sources except the acceptor impurity source in the organic metal source, and only introducing the acceptor impurity source, including: at a third temperature, suspending the introduction of other metal sources except the acceptor impurity source in the organic metal source, and only introducing the acceptor impurity source; wherein the third temperature is lower than or equal to the second temperature. In this embodiment, the third temperature is lower than the second temperature. It can be understood that at a lower temperature, the thermal motion of atoms slows down, which helps the acceptor impurity to find cation vacancies in the lattice to combine with N atoms and stabilize at the lattice position. Therefore, in the time period from t2 to t3, the temperature can be lowered to ensure the effective doping of the acceptor impurity, which is beneficial to increase the hole concentration of the material.

[0089] Furthermore, the range of the difference between the third temperature and the first temperature is ±10°C. It can be understood that if the third temperature is too high, the effect of the acceptor impurity occupying the cation vacancy may not achieve a more ideal effect. If the third temperature is too low, the C content in the material may increase, and the C atoms are introduced into the deep energy level center, so that the deep energy level defects increase. The deep energy level defects act as trap centers to capture free holes, thereby reducing the hole concentration of the material. Therefore, by controlling the range of the difference between the third temperature and the first temperature within a smaller range of ±10°C, a more ideal doping effect can be obtained.

[0090] In this embodiment, step S102 is continuously executed in the reaction chamber executing step S101, and the step of resuming the introduction of the acceptor impurity source is continuously executed in the reaction chamber of step S102, that is, these three steps are sequentially executed in the same reaction chamber. The preparation process of p-type AlGaN material can be understood as three consecutive growth stages; the first growth stage, namely step S101: at a first temperature, an organic metal source and an N source are introduced to grow the p-type AlGaN material; the second growth stage, namely step S102: the introduction of the organic metal source is suspended, and the temperature is maintained at a second temperature for a certain period of time to allow some Ga atoms in the p-type AlGaN material to escape, thereby generating cation vacancies in the p-type AlGaN material, wherein the second temperature is higher than the first temperature, and the difference between the second temperature and the first temperature ranges from 20°C to 200°C, for example, 50°C to 150°C; the third growth stage, namely: at a third temperature, the introduction of other metal sources in the organic metal source except the acceptor impurity source is suspended, and only the acceptor impurity source is introduced, wherein the third temperature is lower than or equal to the second temperature. In this preparation process, the first growth stage and the third growth stage both include the introduction of an acceptor impurity source for p-type doping. Therefore, the temperature of the third growth stage is adjusted to the same as the temperature of the first growth stage, which can ensure the consistency of the material growth conditions. The first temperature of the first growth stage may have been determined as a temperature that can obtain a better doping effect. Controlling the range of the difference between the third temperature and the first temperature within a smaller range of ±10°C can maximize the doping effect and avoid doing more experiments in the third growth stage to verify the temperature that can obtain a better doping effect.

[0091] In this embodiment, please refer to Figure 3 , the third temperature is equal to the first temperature, thereby obtaining a more ideal doping effect, and making it possible to control two temperature gradients in the entire preparation process, namely, controlling the temperature at the first temperature and controlling the temperature at the second temperature, without the need to introduce an additional third temperature gradient, thereby reducing the process difficulty.

[0092] It can be understood that the third temperature is equal to the first temperature means that the third temperature is equal to the first temperature within the error range allowed in the actual preparation. In the actual preparation process, affected by the reaction chamber environment, the input source, the process accuracy and other conditions, the reaction temperature may be difficult to maintain a fixed value, and usually fluctuates within a certain range. Then, when performing the cooling operation, it may be difficult to accurately reduce the temperature to the first temperature value. Therefore, in the actual preparation, the temperature can be controlled to be lowered to near the first temperature, and the difference between the two is within a certain error range, so that the third temperature is approximately equal to the first temperature.

[0093] Optionally, refer to Figure 5 , in the time period from t0 to t1, the preparation method further includes: introducing a carrier gas; wherein the carrier gas includes a mixed carrier gas composed of N2 and H2. It can be understood that pure H2 as a carrier gas can obtain better crystal quality, but it is more difficult to incorporate Mg atoms, which affects the hole concentration of the material. It is easier to incorporate Mg atoms with pure N2 as a carrier gas. This is actually because the surface roughness of the crystal grown with pure N2 as a carrier gas becomes larger, and under pure N2 carrier gas, the C doping content is significantly higher, and a higher C impurity content will form C in the p-type AlGaN material. N -O N The complex becomes a donor, which will compensate for the Mg acceptor and then reduce the hole concentration of the material. Therefore, the use of a mixed carrier gas composed of N2 and H2 can increase the doping amount of Mg atoms while ensuring the quality of the crystal, which is beneficial to improving the performance of the device.

[0094] Optionally, the proportion of N2 in the mixed carrier gas ranges from 10% to 45%. It can be understood that if the proportion of N2 in the mixed carrier gas is low, it may affect the doping effect of Mg atoms and the hole concentration in the material; if the proportion of N2 in the mixed carrier gas is high, it may affect the crystal quality, the electrical properties of the material, and may also affect the C content in the material and the hole concentration in the material. Therefore, within this range, the final prepared material can have a more ideal hole concentration and more ideal performance.

[0095] Furthermore, in the time period from t1 to t2 and / or in the time period from t2 to t3, the proportion of N2 in the mixed carrier gas can be in the range of 15% to 25%, thereby maximizing the doping of Mg atoms, being more conducive to reducing material resistance, and making the performance of the finally prepared p-type AlGaN material better.

[0096] Correspondingly, an embodiment of the present application further provides a p-type AlGaN material, which is prepared using the method for preparing the p-type AlGaN material as described above.

[0097] In some embodiments, p-type AlGaN material can be used as a hole injection layer or ohmic contact layer in an optoelectronic device. It can be understood that p-type GaN material is usually used in the art to prepare a hole injection layer or an ohmic contact layer, but there are problems of severe light absorption and low luminous efficiency; if p-type AlGaN material is used to prepare a hole injection layer or an ohmic contact layer, since the band gap of the p-type AlGaN material is larger than the band gap of the p-type GaN material, the light absorption phenomenon can be effectively reduced. By adjusting the proportion of the Al component to tune the band gap of the material, the light absorption phenomenon can be further reduced and the luminous efficiency can be improved. However, as the proportion of the Al component increases, the activation energy of the acceptor impurity atoms in the p-type AlGaN material is higher, making it difficult to excite and generate enough hole carriers, so that the hole concentration of the material is reduced, resulting in an increase in contact resistance and poor ohmic contact, which restricts the application of p-type AlGaN materials. The p-type AlGaN material provided in the embodiment of the present application has an improved hole concentration, which can then reduce the contact resistance of the material and improve device performance.

[0098] In some embodiments, p-type AlGaN material can be used as an electron blocking layer in optoelectronic devices. Thus, by adjusting the proportion of the Al component, the p-type AlGaN material can have a wide bandgap and a high potential barrier, thereby effectively blocking the leakage of electrons from the multi-quantum well layer to the p-type layer to improve the luminous efficiency. However, as the proportion of the Al component increases, the activation energy of the acceptor impurity atoms in the p-type AlGaN material becomes higher, making it difficult to excite and generate enough hole carriers, which reduces the hole concentration of the material and makes it difficult to effectively play the role of blocking electrons. The p-type AlGaN material provided in the embodiment of the present application has an improved hole concentration, which can then ensure that the p-type AlGaN material plays the role of blocking electrons and improves device performance.

[0099] The embodiment of the present application also provides a method for preparing an ultraviolet optoelectronic device, including: a first step of preparing a main structure of the ultraviolet optoelectronic device, and a second step of preparing an electrode matched with the main structure; the first step includes: preparing a p-type AlGaN material using the above-mentioned method for preparing a p-type AlGaN material to increase the hole concentration of the p-type AlGaN material. Thus, by preparing a p-type AlGaN material using the above-mentioned method for preparing a p-type AlGaN material, the hole concentration of the p-type AlGaN material is increased, thereby making the device have better performance.

[0100] The ultraviolet optoelectronic device may be any ultraviolet optoelectronic device well known to those skilled in the art, for example, optoelectronic devices such as LED and LD.

[0101] Optionally, the main structure of the ultraviolet photoelectronic device includes an electron blocking layer, a hole injection layer and an ohmic contact layer; the p-type AlGaN material layer is the electron blocking layer, the hole injection layer or the ohmic contact layer.

[0102] In the present embodiment, the p-type AlGaN material is not limited to Al atoms, Ga atoms and N atoms, and may contain a small amount of other elements.

[0103] In some embodiments, the first step may include: providing a substrate; growing an n-type AlGaN material layer on the substrate; growing a multi-quantum well layer on the n-type AlGaN material layer; growing a p-type AlGaN material layer as an electron blocking layer on the multi-quantum well layer using the above-mentioned method for preparing p-type AlGaN material; growing a hole injection layer on the electron blocking layer; and growing an ohmic contact layer on the hole injection layer. Thus, the hole concentration in the p-type AlGaN layer prepared by the method for preparing p-type AlGaN material provided in the embodiment of the present application is effectively improved, and while effectively blocking electron leakage, it is beneficial for holes in the p-type AlGaN layer to enter the multi-quantum well layer, increase the hole concentration in the multi-quantum well layer, and increase the probability of electron and hole recombination, thereby improving the luminous efficiency of the device.

[0104] In some embodiments, the first step may include: providing a substrate; growing an n-type AlGaN material layer on the substrate; growing a multi-quantum well layer on the n-type AlGaN material layer; using the above-mentioned method for preparing p-type AlGaN material to grow a p-type AlGaN material layer on the multi-quantum well layer as a hole injection layer; growing an ohmic contact layer on the hole injection layer; or, growing a hole injection layer on the multi-quantum well layer; using the above-mentioned method for preparing p-type AlGaN material to grow a p-type AlGaN material layer on the hole injection layer as an ohmic contact layer. Thus, the hole concentration in the p-type AlGaN layer prepared by the method for preparing p-type AlGaN material provided in the embodiment of the present application is effectively improved, which is conducive to reducing contact resistance and improving device performance.

[0105] The technical solution of the present application will be further described below in combination with experimental data.

[0106] It should be noted that during the experiment, the control variable method was used to experiment on different parameters in the preparation process of p-type AlGaN materials to reflect the influence of different parameters on the performance of p-type AlGaN materials. Therefore, in the following multiple experiments, in the preparation process of different samples in the same experiment, only the parameters that need to be tested are different, and other parameters remain the same. Therefore, the following experiments 1 to 3 respectively test the type of carrier gas, the second temperature and the dwell time in the preparation process of p-type AlGaN materials. When conducting the experiments, except for the above three parameters, the rest of the test steps are the same.

[0107] Specifically, in Experiments 1 to 3, the experimental steps include: providing a substrate; introducing an organic metal source and an N source at a first temperature to grow a U-type AlGaN material layer on the substrate; preparing a p-type AlGaN material on the U-type AlGaN material layer using the above-mentioned method for preparing a p-type AlGaN material; and testing the specific contact resistivity of the p-type AlGaN material; wherein the Al component of the U-type AlGaN material accounts for more than 50%, and the thickness of the U-type AlGaN material ranges from 1 μm to 2.5 μm.

[0108] Therefore, by growing U-type AlGaN material on the substrate, lattice mismatch between the p-type AlGaN material and the substrate can be avoided when the p-type AlGaN material is subsequently grown, and the stress generated when growing the p-type AlGaN material can be effectively alleviated, which is conducive to obtaining p-type AlGaN material with high crystal quality, so as to better test the prepared p-type AlGaN material; the hole concentration and performance of the p-type AlGaN material can be evaluated by the specific contact resistivity of the p-type AlGaN material.

[0109] It can be understood that the substrate may include any suitable substrate known to those skilled in the art, such as a sapphire substrate, a Si substrate, a SiC substrate, an AlN substrate, etc.

[0110] In the experiment, the proportion of the Al component of the p-type AlGaN material can range from 20% to 80%. Therefore, it can be verified that the preparation method of the p-type AlGaN material provided by the present application has an effect on improving the hole concentration of the high Al component p-type AlGaN material. In the following multiple experiments, the proportion of the Al component of the p-type AlGaN material is 60%.

[0111] In the experiment, the thickness of the p-type AlGaN material can range from 200 nm to 300 nm, so as to better test the prepared p-type AlGaN material. In the following experiments, the thickness of the p-type AlGaN material is 300 nm.

[0112] In the experiment, the specific contact resistivity of p-type AlGaN material was tested using the transmission ring process, specifically the Circle Transmission Line Model (CTLM).

[0113] The prepared p-type AlGaN material was used as a test sample, and a pattern was formed on the sample. Figure 6 The circular transmission ring pattern shown in the figure is then deposited with electrode materials. In the figure, the inner ring is designed to have a fixed radius, and the outer ring radius gradually increases to form multiple circular transmission rings with different outer ring radii. During the test, a current I is passed through both sides of the outer ring of the circular transmission ring, and the voltage V is measured to obtain the corresponding resistance R:

[0114] R = (R sh / 2π)*[In(r n / r0)+L t (1 / r n +1 / r0)] (1)

[0115] Among them, r0, r n Respectively represent the inner ring radius and the outer ring radius, L t is the length of the transmission line. Since the difference between the inner ring radius and the outer ring radius is very small, it can be approximately considered that r n =r0, then the resistance R:

[0116] R = (R sh / 2π)*[In(r n / r0)]+R sh L t / πr0 (2)

[0117] ln(r n / r0) as the horizontal axis and R as the vertical axis, and linear fitting is performed on multiple data points. The slope k of the fitted line can be used to s And the intercept R0, get the transmission distance L t And the sheet resistance R sh :

[0118] L t =πr0R0 / R sh (3)

[0119] R sh =2πk s (4)

[0120] Therefore, combining equations (3) and (4), the specific contact resistivity ρ can be calculated: c :

[0121] ρ c =R sh L t 2 =πr0R0 2 / 2k s (5)

[0122] The specific parameters of the controlled variables in the preparation process of Experiments 1 to 3 and the test results of the prepared samples are shown below.

[0123] Experiment 1

[0124] The types of carrier gases used in the preparation of p-type AlGaN materials were experimentally tested, where sample 1 was a p-type AlGaN material prepared using pure N2 as a carrier gas, sample 2 was a p-type AlGaN material prepared using pure H2 as a carrier gas, and sample 3 was a p-type AlGaN material prepared using a mixed carrier gas of N2 and H2, where the proportion of N2 in the mixed carrier gas was 20%.

[0125] The specific contact resistivity of the sample was tested, and the surface roughness of the sample was tested by AFM (Atomic Force Microscope) at a magnification of 20 μm*20 μm.

[0126] Table 1

[0127]

[0128] According to the data in Table 1, combined Figures 7 to 9 Sample 1 prepared with pure N2 as carrier gas has the highest roughness of 0.0125nm and the highest specific contact resistivity of 1.701Ω·cm 2 , further reference Figure 7 The highest point of the crystal surface is 40.9nm, and the lowest point is -50.5nm. It can be seen that the use of pure N2 as a carrier gas makes the crystal quality of the material poor. Although it can provide more positions for Mg atoms to enter, the high defect density directly affects the specific contact resistivity of the p-type AlGaN material. Sample 2 prepared using pure H2 as a carrier gas has the lowest roughness of 0.0037nm and a specific contact resistivity of 0.893Ω·cm 2 , which is higher than the specific contact resistivity of sample 3. Figure 8 The highest point of the crystal surface is 24.9nm, and the lowest point is -26.6nm. It can be seen that although using pure H2 as a carrier gas can obtain better crystal quality, it is not conducive to Mg atom doping, affecting the hole concentration of p-type AlGaN materials and the specific contact resistivity of the material. Sample 3 prepared by using a mixed carrier gas composed of N2 and H2 has a roughness of 0.0074nm and the lowest specific contact resistivity of 0.201Ω·cm 2 , further reference Fig. 9 The highest point on the crystal surface is 32.5nm, and the lowest point is -32.5nm. It can be seen that the use of mixed carrier gas can balance the crystal quality and doping effect and obtain a more ideal specific contact rate.

[0129] Experiment 2

[0130] The second temperature in the preparation process of p-type AlGaN material was experimentally tested. The second temperature was set to 1000°C, 1020°C, 1050°C, 1100°C, 1150°C, 1200°C and 1250°C, and samples 4 to 10 were prepared respectively. It should be noted that in this experiment, the first temperature was 1000°C, and the temperature was not increased when preparing sample 4.

[0131] Table 2

[0132]

[0133] According to the data in Table 2 and Fig.10 It can be seen that when preparing samples 5 to 9, the second temperature is higher than the first temperature, and the specific contact resistivity of samples 5 to 9 is lower than that of sample 4 without heating. As the second temperature increases, the specific contact resistivity of the p-type AlGaN material shows a trend of first decreasing and then increasing. In addition, when preparing sample 10, the second temperature is 1250°C, and the difference between the second temperature and the first temperature reaches 250°C, exceeding 200°C. The specific contact resistivity of sample 10 is 0.139Ω·cm 2 , even higher than the specific contact resistivity of sample 4 without heating. It can be seen that excessive heating will affect the performance of the material. In the temperature range of 1020℃ to 1200℃, it has an acceptable specific contact resistivity, especially in the range of 1050℃ to 1150℃, the specific contact resistivity is less than 0.1Ω·cm 2 , the contact resistivity is on the order of 10 -2 It can be seen that setting the second temperature within this temperature range can more effectively increase the hole concentration of the p-type AlGaN material and reduce the specific contact resistivity.

[0134] Experiment 3

[0135] The experimental test was conducted on the time of pausing the introduction of the organic metal source during the preparation of the p-type AlGaN material. The time was set to 5s, 10s, 15s, 20s and 25s, and samples 11 to 15 were prepared respectively.

[0136] Table 3

[0137]

[0138] According to the data in Table 3 and Fig.11 It can be seen that as time increases, the specific contact resistivity of the p-type AlGaN material shows a trend of first decreasing and then increasing. In addition, within the range of 10s to 20s, the specific contact resistivity is less than 0.1Ω·cm 2 , the contact resistivity is on the order of 10 -2It can be seen that setting the time within this range can more effectively increase the hole concentration of the p-type AlGaN material and reduce the specific contact resistivity.

[0139] At the same time, it can be seen from the data in Table 3 that during the time when the organic metal source is suspended, the thickness of the p-type AlGaN material will increase, and the thickness will continue to increase with time.

[0140] Experiment 4

[0141] Experimental tests were conducted on the application of p-type AlGaN materials in different p-type layers of optoelectronic devices. The optoelectronic device was set not to use p-type AlGaN materials, the hole injection layer of the optoelectronic device used p-type AlGaN materials, and the ohmic contact layer of the optoelectronic device used p-type AlGaN materials, and samples 16 to 18 were prepared respectively. EL (ElectroLuminescence) tests were conducted on samples 16 to 18 to detect the voltage and EL Lop (LuminescenceOptical Power) of the samples at a current of 100mA and verify the photoelectric conversion efficiency (Wall-Plug Efficiency, WPE) of the samples.

[0142] Specifically, the preparation process of sample 16 includes the following steps:

[0143] Step 1: growing an AlN material layer on a sapphire substrate, wherein the growth temperature ranges from 1050° C. to 1250° C., and the thickness ranges from 1.5 μm to 4.0 μm;

[0144] Step 2: Continue to grow an AlGaN material layer on the AlN material layer, wherein the growth temperature ranges from 1050° C. to 1200° C., the Al component grows gradually, and the thickness range of the AlN material layer is from 50 nm to 300 nm;

[0145] Step 3: Continue to grow an n-type AlGaN material layer, wherein the growth temperature ranges from 1000°C to 1150°C, the thickness ranges from 1.8μm to 3.5μm, the Al component is between 40% and 65%, and the Si doping concentration is between 5E+18 and 1E+19;

[0146] Step 4: growing a multi-quantum well layer on the n-type AlGaN material, wherein the growth temperature ranges from 1000°C to 1150°C, the Al component is between 35% and 60%, the thickness of the quantum well layer is between 1nm and 4nm, the thickness of the quantum barrier layer is between 3nm and 12nm, 1-5 cycles are stacked, and the Si doping concentration of the quantum barrier layer is between 6E+17 and 8E+18;

[0147] Step 5: growing a p-type electron blocking layer on the multi-quantum well layer, wherein the growth temperature ranges from 1000° C. to 1250° C., the thickness of the electron blocking layer ranges from 20 nm to 40 nm, the Al component ranges from 50% to 75%, and the Mg doping concentration ranges from 1E+18 to 2E+19;

[0148] Step 6: growing a hole injection layer on the electron blocking layer; specifically, at a temperature of 1000° C., introducing TMGa, TMAl and CP2Mg as organic metal sources, and using a N2 / H2 mixed carrier gas as the growth atmosphere, wherein the proportion of N2 is 50%, wherein the thickness of the hole injection layer ranges from 30 nm to 60 nm, the Al component is between 45% and 70%, and the Mg doping concentration is between 2E+18 and 2E+19;

[0149] Step 7: growing an ohmic contact layer on the hole supply layer; specifically, at a temperature of 950° C., introducing TMGa, TMAl and CP2Mg as organic metal sources, and using a N2 / H2 mixed carrier gas as the growth atmosphere, wherein the proportion of N2 is 50%, wherein the Mg doping concentration is between 1E+19 and 2E+20;

[0150] Step 8: Use chip manufacturing technology to obtain optoelectronic devices.

[0151] The difference between the preparation process of sample 17 and the preparation process of sample 16 lies in the specific preparation process of the hole injection layer in step 6: TMGa, TMAl, CP2Mg and TMIn are introduced as organic metal sources. After a certain period of time, the TMGa, TMIn, TMAl and CP2Mg sources are turned off, the temperature is increased by 50°C, the high-temperature growth is paused for 15 seconds, and then the CP2Mg source is turned on.

[0152] The difference between the preparation process of sample 18 and the preparation process of sample 16 lies in the specific preparation process of the ohmic contact layer in step 7: TMGa, TMAl, CP2Mg and TMIn are introduced as organic metal sources. After a certain period of time, the TMGa, TMIn, TMAl and CP2Mg sources are turned off, the temperature is increased by 50°C, the high-temperature growth is paused for 15 seconds, and then the CP2Mg source is turned on.

[0153] Table 4

[0154]

[0155] According to the data in Table 4, compared with sample 16 which does not use the p-type AlGaN material prepared by the preparation method of the present application as the p-type structural layer, sample 17 uses the p-type AlGaN material as the hole injection layer, and the luminous power increases from 19.2mV to 28.5mV, the brightness increases, and the photoelectric conversion efficiency increases from 2.29% to 4.41%, a significant increase of 92.6%, and the device performance is better; sample 18 uses the p-type AlGaN material as the ohmic contact layer, the luminous power increases from 19.2mV to 23.4mV, the brightness increases, and the photoelectric conversion efficiency increases from 2.29% to 3.29%, an increase of 43.7%, and the device performance is better. It can be seen that the p-type AlGaN material prepared by the preparation method of the present application as the p-type structural layer of the device can enhance the luminous brightness of the device, improve the photoelectric conversion efficiency of the device, and have better performance.

[0156] Experiment 5

[0157] The effect of the ratio of N2 in the N2 / H2 mixed carrier gas on the device performance when preparing p-type AlGaN material was tested. The difference between the preparation process of sample 19 and the preparation process of sample 17 is that the ratio of N2 in step 6 is 20%.

[0158] Table 5

[0159]

[0160] According to the data in Table 5, compared with sample 17 prepared by using 50% N2 N2 / H2 mixed carrier gas, sample 19 uses 20% N2 N2 / H2 mixed carrier gas as the growth atmosphere, the luminous power increases from 28.5mV to 35.1mV, the brightness increases, and the photoelectric conversion efficiency increases from 4.41% to 6.27%, an increase of 42.18%, and the device performance is better. It can be seen that the p-type AlGaN material prepared by using this ratio of N2 / H2 mixed carrier gas as the growth atmosphere can enhance the luminous brightness of the device, improve the photoelectric conversion efficiency of the device, and make it have better performance.

[0161] It should be noted that the p-type AlGaN material preparation method embodiment, p-type AlGaN material embodiment and ultraviolet photoelectronic device embodiment provided in the present application belong to the same concept; the technical features in the technical solutions recorded in each embodiment can be arbitrarily combined without conflict.

[0162] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present application that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present application and do not limit the scope of protection of the patent of this application.

Claims

1. A method for preparing a p-type AlGaN material, characterized in that: include: At a first temperature, introducing an organic metal source and an N source to grow a p-type AlGaN material; wherein the first temperature ranges from 900° C. to 1150° C., and the organic metal source includes an acceptor impurity source; Stopping the introduction of the organic metal source and maintaining the temperature at a second temperature for a certain period of time to allow some Ga atoms in the p-type AlGaN material to escape, thereby generating cation vacancies in the p-type AlGaN material; wherein the second temperature is higher than the first temperature, and the difference between the second temperature and the first temperature ranges from 20° C. to 200° C.; At a third temperature, the introduction of other metal sources in the organic metal source except the acceptor impurity source is stopped, and the acceptor impurity source is introduced, and the acceptor impurity occupies the cation vacancy; wherein the difference between the third temperature and the first temperature is in the range of ±10°C.

2. The method for preparing a p-type AlGaN material according to claim 1, characterized in that: The organic metal source includes an Al source, a Ga source, an In source and a Mg source, and the amount of the In source introduced is less than the amount of the Ga source introduced; The step of introducing an organic metal source and an N source to grow a p-type AlGaN material comprises: introducing the Al source, the Ga source, the In source, the Mg source and the N source to grow an In-doped p-type AlGaN material; The suspending the introduction of the organic metal source to allow some Ga atoms in the p-type AlGaN material to escape includes: suspending the introduction of the Al source, the Ga source, the In source and the Mg source to allow In atoms and some Ga atoms in the p-type AlGaN material to escape; wherein the escape amount of the In atoms is less than the escape amount of the Ga atoms.

3. The method for preparing a p-type AlGaN material according to claim 2, characterized in that: The amount of the In source introduced ranges from 20 sccm to 100 sccm.

4. The method for preparing a p-type AlGaN material according to claim 1, characterized in that: The p-type AlGaN material is at least one of an electron blocking layer, a hole injection layer and an ohmic contact layer.

5. The method for preparing a p-type AlGaN material according to claim 1, characterized in that: The growing of the p-type AlGaN material includes: growing the p-type AlGaN material at a growth rate ranging from 0.05 μm / h to 0.35 μm / h.

6. The method for preparing a p-type AlGaN material according to claim 1, characterized in that: The time ranges from 5s to 50s.

7. The method for preparing a p-type AlGaN material according to claim 6, characterized in that: The time ranges from 10s to 20s.

8. The method for preparing a p-type AlGaN material according to claim 1, characterized in that: The Al component of the p-type AlGaN material ranges from 20% to 90%; The preparation method further includes: introducing a carrier gas; wherein the carrier gas includes a mixed carrier gas composed of N2 and H2, and the proportion of N2 in the mixed carrier gas ranges from 10% to 45%.

9. The method for preparing a p-type AlGaN material according to claim 8, characterized in that: The proportion of N2 in the mixed carrier gas ranges from 15% to 25%.

10. A p-type AlGaN material, characterized in that: The p-type AlGaN material is prepared by the method for preparing the p-type AlGaN material as claimed in any one of claims 1 to 9.

11. A method for preparing an ultraviolet photoelectronic device, comprising: The first step of preparing the main structure of the ultraviolet optoelectronic device, and A second step of preparing an electrode that cooperates with the main structure; Characterized in that the first step comprises: A p-type AlGaN material layer is prepared by using the preparation method of a p-type AlGaN material according to any one of claims 1 to 9, so as to increase the hole concentration of the p-type AlGaN material layer.

Citation Information

Patent Citations

  • A preparation method of a light emitting diode epitaxial wafer and a light emitting diode epitaxial wafer

    CN109103303A

  • P-type gate enhanced GaN-based power device and preparation method thereof, and electronic equipment

    CN115775826A

  • Light emitting devime and fabricating method for the same

    KR1020130047066A